Local Culture in the Dynamics of Islamic Religious Organizations (Study on Muhammadiyah Branch of Padang Lawas Utara District) - Suhendra, Dedy; Hermanto, Mulyadi; Siregar, Sutan; Abidan, Abdul Azis (IBDA` : Jurnal Kajian Islam dan Budaya, 2024)
Muhammadiyah is one of Indonesia's most prominent Islamic religious organizations, growing rapidly as a leading religious organization in health and education. This research examines the challenges faced by the Muhammadiyah branch in the Padang Lawas Utara district. This study explores the dynamics between Muhammadiyah's institutional practices and the cultural frameworks within which they operate. The study utilizes a case study method to provide an in-depth understanding of the interactions between Muhammadiyah's organizational practices and local cultural elements. Data collection involves semi-structured interviews with key informants, participant observation, and document analysis of relevant organizational records and cultural artifacts. Data analysis was conducted using thematic analysis. A triangulation method is employed to ensure the validity and reliability of the data. The findings indicate that while local traditions can enhance the acceptance of Muhammadiyah's reformist ideals, they can also present challenges when cultural norms conflict with the organization's objectives. They are reluctant to accept the Muhammadiyah ideology due to the incompatibility between local culture and Islamic teachings.